What would Wallace do?. Issue 4 (1st August 2022) - Rees, Martin
Abstract : At the start of the 20th century, Alfred Russel Wallace was pessimistic about the possibility of life outside Earth. Martin Rees wonders what he would think now. Abstract: At the start of the 20th century, Alfred Russel Wallace was pessimistic about the possibility of life outside Earth. Martin Rees wonders what he would think now.